Sensitivity of CO2 Flow in Production/Injection Wells in CPG (CO2 Plume Geothermal) Systems - Sofianos Panagiotis Fotias; Vassilis Gaganis (Materials Proceedings)
Geothermal energy is typically produced from underground reservoirs using water as the working fluid to transfer heat energy to surface and eventually to the delivery point. CO2 has been proposed as an alternative working fluid due to its improved mobility, density and its supercritical phase state, leading thus to so-called CPG (CO2 Plume Geothermal) systems. As a positive side effect, the injected CO2 mass circulation in the reservoir can be considered a CO2 storage mechanism, which, depending on the size of the porous medium, may account for few millions of CO2 tons. Moreover, the thermosiphon effect, owned to the significant change of fluid density between the injection (cold) and the production wells (hot) as well as to its change along the wells, significantly reduces the need for pumping, hence the operating costs. In this work, we setup a mathematical model that fully describes flow in the production/injection wells doublet as well as in the geothermal reservoir. Subsequently, the model is used to evaluate the sensitivity of the beneficial effects of circulating CO2 rather than water. Parameters such as reservoir properties, injection temperature and thermal effects, are tweaked to demonstrate the sensitivity of each one to the system performance. The results can be utilized as a guideline to the design of such systems and to the emphasis needed to be paid by the engineers.